2016
DOI: 10.1177/1741659016667438
|View full text |Cite
|
Sign up to set email alerts
|

‘The best three days of my life’: Pleasure, power and alienation in the 2011 riots

Abstract: This article examines one of the less frequently considered elements of riots: the emotions to which they give rise. Based on testimony from interviews with people who took part in the 2011 England riots, it explores the curiosity which drew many onto the streets, the excitement and fear involved in such quickly unfolding and unpredictable events, the impunity that many felt being part of such large crowds, together with the sense of ‘empowerment’ many experienced as a consequence of their involvement. The art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We are by no means the first to highlight the experience of empowerment among participants in the 2011 riots. Newburn et al () have previously shown that empowerment among those who were anti‐police was prevalent and phenomenologically important. Stott et al () and Ball et al () showed that experiences of empowerment among participants in Tottenham led some to travel to new locations to spread the rioting.…”
Section: Discussionmentioning
confidence: 99%
“…We are by no means the first to highlight the experience of empowerment among participants in the 2011 riots. Newburn et al () have previously shown that empowerment among those who were anti‐police was prevalent and phenomenologically important. Stott et al () and Ball et al () showed that experiences of empowerment among participants in Tottenham led some to travel to new locations to spread the rioting.…”
Section: Discussionmentioning
confidence: 99%
“…The largest and most extensive research study of the 2011 riots is the Guardian /LSE's ‘Reading the Riots’, based on 270 interviews with rioters carried out soon after the events (Lewis et al., ; see Newburn, 2016a, 2016b; Newburn, Diski, et al., ; Newburn, Lewis, Addley, & Taylor, ). This work has provided a rich analysis of the experiences of rioters, showing that, together with collective anger, empowerment and joy were evident in actions such as defeating the police (Newburn, Deacon, et al., ). Theoretically, ‘Reading the Riots’ researchers have sought to provide a general criminological analysis of cause and consequences in the 2011 English riots; in effect, they offer a ‘grand theory’ of riot (e.g.…”
Section: Explaining the 2011 English Riotsmentioning
confidence: 99%
“…Traditional representations of participation remain the social benchmark for assessing the political engagement of young people (Pickard, 2016). Therefore, some forms of political mobilisations tend to be systematically disregarded, criticised or even automatically associated with violence by both the media and public officials (Roudet, 2012;Muncie, 2009;Pickard, 2009;Newburn, et al, 2016). This rejection of their efforts to express a political message can be a source of cynicism (Cockburn and Cleaver, 2012;Roudet, 2012) or frustration (Boire, 2015;Benedicto and Luz Morán, 2016).…”
Section: Discussion: Protesting the Neo-liberal World Ordermentioning
confidence: 99%
“…Indeed, young people's expression and action seem stronger when it takes other, less institutionalised forms (Loncle, et al, 2012;Gallant and Garneau, 2016), especially those that channel dissent (Roudet, 2012) and/or individuality (Pastinelli, 2013). These include innovative forms of demonstrations (such as flash mobs or the Occupy and Indignados movements), political citizenship expressed through cultural practices (Poirier, 2017), or even unplanned riots (Newburn, et al, 2016;Bertho, 2016). Young people's online participatory experience (Caron, 2014) also takes many shapes: the use of Facebook and other social media to organise various political action, political expression on blogs, Twitter and YouTube (Millette 2015;Caron, 2014;Jenkins and Carpentier, 2013).…”
Section: Recognising Youth Political Actionmentioning
confidence: 99%